Information Ecology in The Context of General Ecology: A Review - Pradhan , Bibhuti B (International Journal of Psychosocial Rehabilitation, 2019)
The environmental method studied in this paper is a new level of knowledge studies. This allows for a better understanding of information processes in society, as well as a more effective development of information processing systems. Information ecology offers a conceptual framework for the analysis of data, the production of knowledge and the flow of information within a multidimensional context. This paper describes and analyses ecological studies in a variety of fields, from biology to technology, to sociology, to knowledge and information. Subsequently, elements of the general ecology building methodological and philosophical foundation for information ecology were presented and a concise definition of information ecology was developed and information ecology further developed as a methodological basis for information studies, generally based on the concepts and principles of the general information theory [1]. Complexity, ambiguity, and non-linearity are part of information ecology and are addressed today by exploring multiple types of knowledge, developing vocabulary for the information system, and recognizing the need for intermediation.